MECHANISMS FOR IMPROVING MANAGEMENT COMPETENCE OF LEADERS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Khalmonov Umid Ochilovich (Journals Park Publishing, 2024)
This article will provide feedback and feedback on the mechanisms of improving the management competence of the heads of the preschool educational organization. Improving the management competence of heads of preschool educational organizations is crucial for the delivery of high-quality early childhood education. Effective management in these settings not only ensures the smooth operation of daily activities but also plays a pivotal role in fostering an environment conducive to the developmental needs of young children.
Keywords: Management competence, preschool education, leadership skills, early childhood education, staff management, professional development, educational expertise, regulatory compliance, financial management, strategic planning.